2015
DOI: 10.4238/2015.december.29.11
|View full text |Cite
|
Sign up to set email alerts
|

Rutin, quercetin, and free amino acid analysis in buckwheat (Fagopyrum) seeds from different locations

Abstract: ABSTRACT. In this study, five common buckwheats and nine tartary buckwheats grown at different locations were analyzed for the contents of rutin, quercetin, and amino acids by high-performance liquid chromatography and spectrophotometry. The rutin content was higher than quercetin in buckwheat seeds. Rutin content was in the range from 0.05 (0.05 g per 100 g dry seeds) to 1.35% of buckwheat seeds. Quercetin content varied from 0.01 to 0.17% and in some common buckwheats it was even difficult to detect. Compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…We found that the rutin content of seed was typically higher than that of quercetin, indicating that rutin is the major flavonoid in buckwheat seeds. These observations are consistent with the findings of Bai et al (2015) and Raina and Gupta (2015), who reported rutin as the major flavonoid in buckwheat seeds. Overall, we found that the rutin content in common buckwheat seeds ranged from 7.22 to 47.86 mg/100 g DW, averaging 18.52 mg/100 g DW.…”
Section: Evaluation For Rutin and Quercetin Contentsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the rutin content of seed was typically higher than that of quercetin, indicating that rutin is the major flavonoid in buckwheat seeds. These observations are consistent with the findings of Bai et al (2015) and Raina and Gupta (2015), who reported rutin as the major flavonoid in buckwheat seeds. Overall, we found that the rutin content in common buckwheat seeds ranged from 7.22 to 47.86 mg/100 g DW, averaging 18.52 mg/100 g DW.…”
Section: Evaluation For Rutin and Quercetin Contentsupporting
confidence: 93%
“…Buckwheat shows a wide diversity in growth traits related to seed size and shape, seed coat and flower color, grain yield, and the content of phenolic components. Flavonoid contents could vary based on varietal variability (Oomah et al 1996;Kalinová and Dadáková 2006;Brunori et al 2009;Qin et al 2010;Kiprovski et al 2015;Raina and Gupta 2015), sowing time (Omidbaigi and Mastro 2004;Jinfeng et al 2010;Hyun et al 2018), location (Bai et al 2015), growth stages (Bystricka et al 2014), environmental factors such as UV radiation, light (Suzuki et al 2005;Kim et al 2006;Nam et al 2018) and area of collection (Seo et al 2013;Bai et al 2015;Yu et al 2019). Oomah et al (1996) reported that variation is phenolic acids in buckwheat is mainly due to cultivar, seasonal effects, and their interaction, whereas growing location has no effect.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin (3,3ʹ,4ʹ,5,7-pentahydroxyflavone) is one of the most prevalent dietary flavonoids found in many plant-based foods including onions, berries, buckwheat, and green leafy vegetables (Bai et al, 2015;Hakkinen, Karenlampi, Heinonen, Mykkanen, & Torronen, 1999;Lesjak et al, 2018;Patil, Pike, & Yoo, 1995). Quercetin is naturally present as an aglycone or in its β-glycoside forms in fruits and vegetables.…”
mentioning
confidence: 99%
“…Rutin (quercetin-3-O-rutinoside, Figure 1B) is one of the major quercetin glucosides, and is widely distributed in plant foods such as buckwheat seeds, coriander, and nalta jute [14,15]. However, its bioavailability has been reported to be lower than that of quercetin aglycone [16].…”
mentioning
confidence: 99%